1998
DOI: 10.1038/sj.onc.1202059
|View full text |Cite
|
Sign up to set email alerts
|

Fungal metabolite FR901228 inhibits c-Myc and Fas ligand expression

Abstract: Activation of T lymphocytes often leads to cellular activation, production of cytokines, entry into cell cycle, and expression of Fas (CD95) and Fas ligand (FasL). Although it is well established that the interaction of Fas and FasL results in apoptosis, mechanisms for regulated expression of Fas and FasL are unclear. Our previous work with antisense oligodeoxynucleotides suggested that the protooncogene c-myc is obligatory for activationinduced apoptosis. To study the relationship between cmyc and the Fas/Fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 24 publications
3
49
0
Order By: Relevance
“…The latter possibility is supported by evidence that transcription of the CD95/Fas ligand is targeted for activation by many apoptotic stimuli, including TCR activation through NF-kB (Kasibhatla et al, 1999), DNA damage and other stresses through NF-kB, the Jnk pathway (AP-1), and Egr-3 (Faris et al, 1998;Kasibhatla et al, 1998;Mittelstadt and Ashwell, 1998). Sensitization by c-Myc in Rat1 ®broblasts was not due to upregulation of CD95/Fas or CD95/Fas ligand, although recent evidence suggests that CD95/ Fas ligand may be a target for activation by c-Myc in other cell types (Wang et al, 1998a). In any case, the biological data indicates that c-Myc can sensitize cells to CD95/Fas ligand by acting at some point downstream of the receptor.…”
Section: Regulatory Connections Between C-myc and Death Receptorsmentioning
confidence: 89%
See 2 more Smart Citations
“…The latter possibility is supported by evidence that transcription of the CD95/Fas ligand is targeted for activation by many apoptotic stimuli, including TCR activation through NF-kB (Kasibhatla et al, 1999), DNA damage and other stresses through NF-kB, the Jnk pathway (AP-1), and Egr-3 (Faris et al, 1998;Kasibhatla et al, 1998;Mittelstadt and Ashwell, 1998). Sensitization by c-Myc in Rat1 ®broblasts was not due to upregulation of CD95/Fas or CD95/Fas ligand, although recent evidence suggests that CD95/ Fas ligand may be a target for activation by c-Myc in other cell types (Wang et al, 1998a). In any case, the biological data indicates that c-Myc can sensitize cells to CD95/Fas ligand by acting at some point downstream of the receptor.…”
Section: Regulatory Connections Between C-myc and Death Receptorsmentioning
confidence: 89%
“…Third, inhibition of CD95/Fas signaling blocks apoptosis but not proliferation by cMyc in Rat1 ®broblasts (Hueber et al, 1997). CD95/ Fas ligand (CD95L/FasL) may be an additional target of c-Myc in certain cell types (Wang et al, 1998a;D Sakamuro and GC Prendergast, unpublished observations). Lastly, interaction between c-Myc and Bin1 is necessary to activate apoptosis but dispensable to drive proliferation or malignant transformation, in both ®broblast and epithelial cell models (Sakamuro et al, manuscript submitted).…”
Section: Modi®ed Dual Signal Model For C-myc Functionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several of these transcription factors have been shown to directly regulate CD95L transcription in response to TCR activation. In addition, we have reported that activation-induced CD95L expression requires the participation of the protooncogene c-myc (31).…”
mentioning
confidence: 99%
“…Accordingly, AML1/ETO which is present in about 12% of AML cases is ETO-positive hematopoietic cells and, by another group, in various breast cancer cell lines. 34 Downregulation of c-MYC by DACi has been reported previously [35][36][37][38] and may also account for inhibition of LSC capacity. Here, a reduced protein level of c-MYC was recognized as early as 6 h after addition of DACi (data not shown), suggesting that c-MYC repression is a direct effect of DACi treatment.…”
Section: Discussionmentioning
confidence: 99%